Nanoparticles for enhancing mechanical properties of fly ash concrete. (2016) - Kumari, Kalpana; Preetha, R.; Ramachandran, D.; Vishwakarma, Vinita; George, Rani. P.; Sundaramurthy, C.; Kamachi Mudali, U.; Sivathanu Pillai, C.
Abstract: Fly ash is used in concrete industry to reduce the amount of cement and to enhance durability of concrete. Some early-age performance issues of fly ash concrete are, delayed setting time, low early-age strength, and a more stringent curing conditions. To overcome this deficiency, nano modifications are adopted. This study is attempted to understand the effect of nano TiO2 (NT), nano CaCO3 (NC) particles and a combination of NT and NC particles (NTC) on various properties like compressive strength, workability and durability of fly ash concrete by partial replacement of cement. NT and NC particles with average diameter of 50-70 nm were used with six different contents ranging from 0.5 to 3% by weight of cement, with an increment of 0.5%. The results showed that addition of NT particles up to a maximum replacement level of 3.0% produced concrete with improved strength, whereas addition of NC and NTC particles in the mix showed higher strength up to 2% and thereafter it decreased. Workability of fresh concrete increased at 0.5% addition of all the three nano particles and thereafter, though it decreased for given water to powder content, the mixes were workable. This was confirmed with consistency tests. The fresh and hardened properties along with low rapid chloride penetration values and high pH values highlight the advantages of nano modification of flyash concrete.